SURVEYING THE ANTHROPOGENIC IMPACT OF THE MOLDAU RIVER SEDIMENTS AND NEARBY SOILS USING MAGNETIC SUSCEPTIBILITY - Knab M.; Hoffmann V.; Petrovský E.; Kapička A.; Jordanova N.; Appel E. (My University, 2006)
Measuring magnetic susceptibility is a method which is used to estimate the amount of magnetic particles in soils, sediments or dusts. Changes in magnetic susceptibility can be due to various reasons: input from different sources of sediments, e.g. from different soils or rocks, atmospheric fallout of anthropogenic dusts containing magnetic particles produced by fossil fuel combustion, steel production or road traffic. In the case of river sediments, input from the catchment is of primary significance. The main aim of this investigation was to test the potential of magnetic susceptibility screening in identifying the effect and significance of anthropogenic activities in an area with complex geological conditions. We investigated the magnetic susceptibility of riverbed sediments of the largest river of the Czech Republic, the Moldau river. Besides that, the magnetic signal of nearby topsoils as well as of outcropping bedrocks in the vicinity of the river was examined. In the upper 300 km of the river, the magnetic enhancement of the river sediments can be linked to anthropogenic activities. Positive correlations were found in the river sediments between the contents of Cu and Zn and magnetic susceptibility, while Fe, Mn and Ni did not show a correlation with magnetic susceptibility. However, the major geogenic magnetic anomaly in the area around the Slapy dam has made it impossible to unambiguously interpret the magnetic signal in terms of anthropogenic impact in the last 80 km downstream.
Keywords: MAGNETIC SUSCEPTIBILITY; MAGNETIC PARTICLE; MAGNETIC ANOMALY; RIVER SEDIMENT; BOHEMIAN MASSIF